The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/joim.13127
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamics of primary aldosteronism associated with adrenocortical adenoma: insights from bioimpedance cardiography measurements

Abstract: Click here to see the Original article by Choudhary et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Volume status and BP regulation are intimately correlated [ 37 ]. Earlier reports have shown overhydration and increased ECW volume in primary aldosteronism vs. essential hypertension [ 8 12 ], whereas BP reduction has been reported to correlate with plasma volume contraction in primary aldosteronism [ 38 ]. We observed ∼1 l ECW excess in the primary aldosteronism patients, which was normalized by adrenalectomy and spironolactone-based treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume status and BP regulation are intimately correlated [ 37 ]. Earlier reports have shown overhydration and increased ECW volume in primary aldosteronism vs. essential hypertension [ 8 12 ], whereas BP reduction has been reported to correlate with plasma volume contraction in primary aldosteronism [ 38 ]. We observed ∼1 l ECW excess in the primary aldosteronism patients, which was normalized by adrenalectomy and spironolactone-based treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Early investigations using radiolabelled tracers in small patient groups indicated that aldosterone excess is characterized by volume overload [8,9]. Recent studies utilizing bioimpedance have confirmed extracellular fluid overload in primary aldosteronism patients [10][11][12]. Aldosterone excess increases growth factors and collagen accumulation in the arteries [6,7].…”
mentioning
confidence: 99%